Evaluation of Nutrient Distribution in Soil, Leaf Nutrient Content and Yield of Apricot (Prunus aremeniaca L.) under Drip Fertigation with Different Fertilizers - Jatinder Nath Raina (Research Highlights in Agricultural Sciences Vol. 8, 2023)
Nutrient distribution in soil, leaf nutrient content and yield of apricot (Prunus aremeniaca L) as influenced by drip fertigation and conventional fertilization with water soluble fertilizers were evaluated through field trials for three years on ‘Incepstisols’ at Nauni, Solan, Himachal Pradesh. The cultivated variety of apricot was New Castle. Drip fertigation with 100, 75 and 50% recommended dose (RD) each of conventional fertilizer (CF) and water-soluble fertilizers (WSF) besides conventional soil fertilization both under irrigated and rainfed conditions were tried in triplicate. Iso-moisture curves were developed to determine the water distribution pattern under drip irrigation. The results demonstrate that lower depths (30-45 cm) under conventional irrigation registered much higher water content compared to drip irrigation. Similar trend in depth-wise distribution of water at different lateral distances from emitters was observed under drip and conventional irrigation system. The majority of the applied nutrients during fertigation remained in the surface layers, whereas N and K moved to lower depths under soil fertilisation plus irrigations. The NO3-N concentration in the upper soil layers was higher with drip fertigation than with conventional soil fertilisation, implying higher leaching losses with the latter. The NO3-N content was low beneath the emitters and grew with increasing lateral distance from the emitter up to 15 cm before declining. The NH4-N concentration was greater under the emitters and lowered both vertically and laterally. When drip fertigation was used instead of soil fertilisation, the leaf nutrient content was higher. Fertigation produced significantly more apricot fruit weight and yield than soil fertilisation. Drip fertigation with WSF resulted in a higher fruit yield than CF. The regression analysis of data on fruit yield and tried fertiliser levels revealed that the optimum levels for CF and WSF for drip fertigation were 67 and 70% of RD, respectively. Thus, fertigation could save approximately 30% of the fertilisers used. The results conclusively proved that drip fertigation holds a great potential since it improved the fruit size and weight of apricot significantly over soil fertilization with conventional surface irrigation.